Conference Record of the Twenty-Eighth IEEE Photovoltaic Specialists Conference - 2000 (Cat. No.00CH37036)
DOI: 10.1109/pvsc.2000.916126
|View full text |Cite
|
Sign up to set email alerts
|

Thin HI-ETA/sup (R)/ space silicon solar cells with improved end-of-life performance

Abstract: In this paper we report on two new silicon space solar cell structures of our trademarked HI-ETA@ family which are designed for improved EOL (end-of-life) performance and low weight. The 2iTHI-ETA@3-ID thin (100-1 30pm) HI-ETA" cell with integrated diode is qualified and in large volume production, its efficiency figures are 17.3% at BOL (beginning-of-life) and 12.5% at EOL (1 E l 5 (1 MeV)e' IC").The locally thinned (50pm) cell is still under development, its mechanical structure is sound as already proven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For example, a locally thinned waffle-like cell was proposed for space silicon solar cell in 2000. Strobl et al reported a 15.8% efficiency silicon solar cell with a thickness of 50 μm in the locally thinned regions and 130 μm for the frames 25 . But other details of this structure are particularly underreported.…”
mentioning
confidence: 99%
“…For example, a locally thinned waffle-like cell was proposed for space silicon solar cell in 2000. Strobl et al reported a 15.8% efficiency silicon solar cell with a thickness of 50 μm in the locally thinned regions and 130 μm for the frames 25 . But other details of this structure are particularly underreported.…”
mentioning
confidence: 99%